2016
DOI: 10.1097/bpo.0000000000000557
|View full text |Cite
|
Sign up to set email alerts
|

A Reliable and Valid Objective Structured Assessment of Technical Skill for the Application of a Pavlik Harness Based on International Expert Consensus

Abstract: Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…While the OSATS metric has been extensively utilized and validated for the evaluation of resident’s performance of technical skills, 7 , 9 , 10 , 25 its use as a tool to evaluate the efficacy of simulation laboratories has only been recently described. 11 16 , 26 Anderson and colleagues suggested that any study that utilized the OSATS as a stand-alone assessment measure ignored critical objective assessments regarding the end product of the tested technical procedure.…”
Section: Discussionmentioning
confidence: 99%
“…While the OSATS metric has been extensively utilized and validated for the evaluation of resident’s performance of technical skills, 7 , 9 , 10 , 25 its use as a tool to evaluate the efficacy of simulation laboratories has only been recently described. 11 16 , 26 Anderson and colleagues suggested that any study that utilized the OSATS as a stand-alone assessment measure ignored critical objective assessments regarding the end product of the tested technical procedure.…”
Section: Discussionmentioning
confidence: 99%
“…While the OSATS metric has been extensively utilized and validated for the evaluation of resident's performance of technical skills, [10][11][12][13][14][15] its use as a tool to evaluate the efficacy of simulation laboratories has only been recently described. 6,8,9,26 Anderson and colleagues suggested that any study that utilized the OSATS as a stand-alone assessment measure ignored critical objective assessments regarding the end product of the tested technical procedure. 27 For this reason, we supplemented the OSATS evaluation with direct evaluation of pedicle screw placement.…”
Section: Discussionmentioning
confidence: 99%
“…Verbal instructions were later incorporated as narration, as shown in Video 1 (online). The steps and instructions provided in the video followed those previously identified in a validated OSATS for Pavlik harness application 15 . Video editing was performed using Adobe Premiere Pro software (Adobe Systems) and was timed to allow the viewer the opportunity to practice on the simulator model as the steps were explained on the video.…”
Section: Methodsmentioning
confidence: 99%
“…evaluated all videos using the OSATS and a global rating scale (GRS) for the assessment of performance and final product, which are specific to Pavlik harness application. The OSATS, developed according to international expert consensus using Delphi methodology, is a twenty-five-item rating scale that evaluates the steps required for appropriate Pavlik harness application 15 . Inter-rater and test-retest reliability of all three measures are considered excellent at, respectively, 0.96 and 0.98 for the OSATS; 0.90 and 0.93 for the GRS performance; and 0.93 and 0.94 for the GRS product 15 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation